Development of E-colands (Electronic Comic of Peatlands) for Junior High School Mathematics Learning - Putri Sasalia S; Ramayanti Agustianingsih; Demitra Demitra (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
Low mathematical literacy among Indonesian students, as indicates by PISA results, highlights the need for innovative and contextual learning media that connect mathematics with real-life situations. This study aimed to develop and examine the feasility and praticality of E-Colands (Electronic Comic of Peatlands) as a mathematics learning medium for junior high school students in Central Kalimantan. The research employed a research and development method using the ADDIE model, limited to the Analysis, Design, Development, and Implementation stages. E-Colands was designed as a digital comic integrating matematical literacy tasks with peatland contexts encountered in students’ daily lives. Product feasibility was assesed through expert judgment by material and media experts using Likert-scale validition instruments. Practicality was evaluated through student response questionnaires administered to 75 students from grades VII, VIII, IX selected through purposive sampling. The results showed very high level feasibility, with validation scores of 91.25% form material experts and 89.29% from media experts. Students responses indicated good practicality, with an overall score of 80.49%, expecially in language clarity, media design, and ease of use. These findings suggest that E-Colands is a valid and practical learning medium to support contextual mathematics learning and enhance students’ mathematical literacy.